2015
DOI: 10.1007/s12010-015-1955-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus on Biochemical Composition of Microalgae Polyculture Harvested from Phycoremediation of Piggery Wastewater Digestate

Abstract: The effects of nitrogen (N) and/or phosphorus (P) starvation on the biochemical composition of native microalgae Chlorella spp. polyculture obtained from the phycoremediation of swine wastewaters were investigated. Microalgae-specific growth rate of 1.2 day(-1) was achieved (30.3 mg L(-1) day(-1)). PO4 (-2) and NH3 were completely removed from swine digestate effluent after 3 and 11 days, respectively. Microalgae harvested immediately after nutrient removal showed high protein (56-59 %) and carbohydrate (25-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 34 publications
2
26
1
2
Order By: Relevance
“…These data were in agreement with previous reports that described carbohydrates, proteins and lipids contents in polyculture microalgae is typically within 8e56, 10e52, and 1.9e40%, respectively (Prajapati et al, 2013a). The measured low lipid content was probably associated with high nitrogen content present in swine wastewater digestate which is a nutrient required to induce cellular storage of protein and carbohydrates at the expenses of lipids (Michelon et al, 2015;Bruton et al, 2009;Matsui and Koike, 2010;Prajapati et al, 2013a, b;Wahidin et al, 2014;Zhang et al, 2015). After 25 days of exposure to nutrient-free medium, microalgae biomass showed 54.6 ± 2.6, 24.1 ± 2.4 and 16.9 ± 0.8% of carbohydrate, protein and lipid, respectively (Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These data were in agreement with previous reports that described carbohydrates, proteins and lipids contents in polyculture microalgae is typically within 8e56, 10e52, and 1.9e40%, respectively (Prajapati et al, 2013a). The measured low lipid content was probably associated with high nitrogen content present in swine wastewater digestate which is a nutrient required to induce cellular storage of protein and carbohydrates at the expenses of lipids (Michelon et al, 2015;Bruton et al, 2009;Matsui and Koike, 2010;Prajapati et al, 2013a, b;Wahidin et al, 2014;Zhang et al, 2015). After 25 days of exposure to nutrient-free medium, microalgae biomass showed 54.6 ± 2.6, 24.1 ± 2.4 and 16.9 ± 0.8% of carbohydrate, protein and lipid, respectively (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The physicochemical characteristics of the growth medium play a major role on microalgae intracellular composition changes. To illustrate, the intrinsic nitrogen and phosphorous-rich characteristics of swine wastewater digestate, used as growth medium for microalgae, is likely to stimulate intracellular storage of carbohydrate and/or protein at the expenses of lipid (Michelon et al, 2015;Bruton et al, 2009;Matsui and Koike, 2010;Prajapati et al, 2013b), thus decreasing the potential of this biomass from reaching its highest methane yields. It may be possible, however, to overcome this limitation by stress-inducing changes in cellular chemical composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This considerable intra‐genus variability in the CP concentration also applied to the other genera. Different studies have shown that protein concentration can be affected by factors such as temperature (Morris, Glover, & Yentsch, ), light intensity (Morris et al., ), salinity (Khatoon et al., ) and N (Michelon et al., ; Piorreck, Baasch, & Pohl, ) or phosphorus supply (Healey & Hendzel, ; Michelon et al., ). Furthermore, the time of harvest may have led to differences in the CP concentration as CP levels change during algae growth phases (Fernández‐Reiriz et al., ; Piorreck & Pohl, ; Whyte, ).…”
Section: Resultsmentioning
confidence: 99%
“…The major biomolecules accumulated in microalgae are carbohydrates, proteins, and/or lipids. It was commonly reported in the literature that the variation in algal biochemical composition is responding results of the changing of cultivation conditions such as pH, temperature [26], light [26], salinity, metal contents and nutrients availability [27,28]. Majority of studies investigating growth of microalgae in synthetic media demonstrated that nitrogen and/or phosphorous starvation improves accumulation of lipids and/or carbohydrates [28].…”
Section: Biochemical Composition Of Algal Biomassmentioning
confidence: 99%